0
$\begingroup$

I was asked to find the limit of the following:

$$\lim_{x\to -1}\frac{\sqrt {x ^ 2 + 8} - 3}{x + 1} $$

I have tried using the Limit Laws but am always getting $ \frac {0}{0} $. The answer given is $-\frac {1}{3} $. Can someone give me some hints to arriving at the answer?

$\endgroup$
0

3 Answers 3

3
$\begingroup$

Hint:

Try to expand the fraction like this:

$$ \lim_{x \to -1} \frac{\sqrt{x^2+8}-3}{x+1} \cdot \frac{\sqrt{x^2+8}+3}{\sqrt{x^2+8}+3}. $$

$\endgroup$
1
  • $\begingroup$ @ALGEAN Thanks for the edit! Those curly brackets$\ldots$ $\endgroup$
    – quapka
    Feb 2, 2014 at 9:42
2
$\begingroup$

$$\lim_{x\to -1}\frac{(\sqrt {x ^ 2 + 8} - 3)(\sqrt {x ^ 2 + 8} + 3)}{(x + 1)(\sqrt {x ^ 2 + 8} + 3)} $$ $$\lim_{x\to -1}\frac{x^2+8-9}{(x + 1)(\sqrt {x ^ 2 + 8} + 3)} $$ $$\lim_{x\to -1}\frac{(x+1)(x-1)}{(x + 1)(\sqrt {x ^ 2 + 8} + 3)}$$ $$=\frac{-2}{6}=\frac{-1}{3}$$

$\endgroup$
2
$\begingroup$

$$ \lim_{x\to -1}\frac{\sqrt {x ^ 2 + 8} - 3}{x + 1} = \lim_{x\to -1} \frac{\sqrt {x ^ 2 + 8} - 3}{x + 1} \frac{\sqrt{x^2+8}+3}{\sqrt{x^2+8}+3} = \lim_{x\to -1} \frac{x^2+8-9}{(x+1)(\sqrt{x^2+8}+3)}. $$ Now simplify $\frac{x^2-1}{x+1}$ and compute the limit.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.